LEGAL ACTION AGAINST THE DECISION OF THE CONSTITUTIONAL COURT - Deny Riswanto; Gunawan Widjaja (Adisam Publisher, 2025)
Legal remedies are measures provided by law to individuals or legal entities for specific purposes to challenge a court ruling as a means for parties dissatisfied with a court ruling deemed inconsistent with their wishes, failing to meet the standards of justice, as judges are also human beings who may make errors or omissions, thereby rendering an incorrect decision or favouring one party over another. Decisions of the Constitutional Court have a special characteristic, namely they are final and binding and apply in accordance with the principle of erga omnes, meaning they cannot be subject to any further legal action. Until now, if there are decisions of the Constitutional Court ( ) that are deemed to violate regulations, the maximum action taken is to conduct an Ethics Code Review of the Constitutional Court Justices by the Constitutional Court's Ethics Council. However, even if the Constitutional Court Justices are found to have violated the Ethics Code, their decisions remain valid and must be enforced, leading to controversy and public unrest. Therefore, it is time for the Constitutional Court to establish a legal remedy institution called the Objection Institution. In this regard, a solution to establish this Objection Institution can be pursued by adopting or using the rules applied in the examination of Simple Lawsuits in District Courts as a comparison. This study employs a normative legal research method, as the research objective is the law or legal principles, specifically the rules governing Simple Lawsuits, as a basis for comparison regarding the establishment of a Legal Remedies Institution at the Constitutional Court. The analytical method used is qualitative, employing authentic, grammatical, and systematic interpretations.